PENERAPAN APLIKASI PENJUALAN ONLINE BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA TOKO SUMBER MULYO DI KABUPATEN KUDUS - Heru Saputro; Danang Mahendra (Jurnal DISPROTEK, 2019)
Abstract The increasing business competition between buying and selling shops to get customers has caused building shops to compete to provide the best service for their customers. Consumer satisfaction is the key to building long-term relationships between customers and building stores. Sumber Mulyo Shop which is four in Ds. Piji Rt.1 Rw.2 Dawe Kudus is engaged in buying and selling building materials. The customer service system that is currently available at the Sumber Mulyo Shop is still utilizing for the process of buying and selling and service manually, namely when in the store to respond to customer complaints. Therefore, complaints are not confidential to building shops. The registration process is still done by recording documents, in recording documents causing the customer service takes longer if one day is needed. In making the registration data report member marketing will be difficult in managing store data so that in recording member transaction data there will be many errors. The method of applying the system used in this study is the method of System Development Life Cycle (SDLC), Unified Modeling Language (UML), and using a web-based programming language, PHP. This CRM service system makes it easy for customers to register members, provide input in the form of criticism and suggestions, and can provide convenience for Sumber Mulyo Shop owners for web-based data processing. In this study using this system needs analysis through a SWOT analysis. Keywords: Customer Relationship Management (CRM), Customers, SDLC (System Development Life Cycle), SWOT Analysis.